Dynamic structural equation modelling evaluating the progressively lowered stress threshold as an explanation for behavioural symptoms of dementia. (3rd February 2022) - Pickering, Carolyn E. Z.; Yefimova, Maria; Wang, Danny; Maxwell, Christopher D.; Jablonski, Rita
Abstract: Aim: To evaluate the progressively lowered stress threshold (PLST) conceptual model as an explanation for behavioural symptoms of dementia and test several of its hypothesized propositions. The PLST model suggests that due to impairments in coping, persons living with dementia have a reduced threshold for stress and respond with more behavioural symptoms of dementia as stress accumulates throughout the day. Design: Intensive longitudinal design. Methods: A sample of N = 165 family caregivers completed brief daily diary surveys for 21 days between the dates of 7/2019 and 8/2020, reporting on a total of 2841 days. Dynamic structural equation modelling was used as the analytic technique to examine the impact of caregiver and care recipient environmental stressors on the diversity of behavioural symptoms of dementia to account for the nested data structure and autoregressive relationships. Findings: Results show direct relationships between environmental stressors and diversity of behavioural symptoms of dementia that same day and the following day. Conclusion: Findings provide support for the PLST model propositions. Further, findings suggest an extension to the conceptual model is warranted given evidence of an exposure/recovery trajectory and the lagged effects of stress exposure on behavioural symptoms of dementia presentation. Impact: This study tested whether a commonly used nursing model does in fact explain the occurrence of behavioural symptoms of dementia. The main findings support using the model as an intervention framework and suggest the model should be adapted to consider recovery trajectories. Since behavioural symptoms of dementia represent complex and dynamic temporal phenomena, traditional longitudinal assessments and analyses are an insufficient measurement modality for testing models. Findings inform the design of environmental‐modification type interventions for behavioural symptoms of dementia management and the methods to evaluate such interventions.